Succession processes in the living surface cover of unclosed forest cultures of quercus robur l. in wet loam conditions of Zhytomyr Polissya - Ivaniuk, I.D.; Fuchylo, Ya.D.; Ivaniuk, T.M. (Forestry, Forest, Paper and Woodworking Industry, 2021)
After continuous felling of oak stands and creation of forest crops on the cutting areas, dynamic, mosaic plant groups are formed in the humid conditions of Zhytomyr Polissya, consisting of remnants of forest species and meadow and ruderal plants that settled after deforestation. On cutting areas, the species saturation of the grass-shrub tier (83 species) is much higher than in fresh loam conditions (50 species). On biennial cutting areas, plant communities are similar in species composition to the vegetation of annual cutting areas. Some forest species disappear from the floristic composition of the groups, in particular: Convallaria majalis L., Galium intermedium Schult, Polygonatum odoratum (Mill.) Druce, Hypericum maculatum Crantz and others, resulting in reduced floristic saturation up to 64 species. The projective cover of preserved forest species is significantly reduced, and ruderal, invasive and meadow species continue to play a leading role in grass formation. Typical forest species continue to fall on the three-year-old fellings from the floristic composition of the cenosis, in particular Pteridium aquilinum (L.) Kuhn, Rubus saxatilis L., Calamagrostis arundinacea (L.) Roth., Cruciata glabra (L.) Ehrend.) and others. Some forest species are restored under the tent of undergrowth. In three-year-old plant communities, ruderal species play a significant role, in particular: Galeopsis tetrahit L., Galeopsis bifida Boenn., Persicaria minor (Huds. Opiz), Erigeron canadensis L. and others, the projective coverage of which is gradually decreasing. In seven-ten-year-old oak forest stands in the conditions of wet soil, the closure of the stands of the stand, as in fresh conditions, is 0.80-0.85, but the species composition of the first tier is much richer. The undergrowth in floristic composition and coenotic structure is also similar to the undergrowth of 120-year-old coenoses. Its closure is usually 0.50. Species saturation (up to 61 species) increases in the grass-shrub tier. Light-loving ruderal species fall out, a number of typical forest plants appear, and the restoration of the coenotic structure of the phytocenosis is completed. A characteristic feature of living aboveground cover in wet soil, compared to fresh soil, is the presence of wetland plants, which appear in the first year due to lightening of the soil surface and increase its humidity, and continue to grow in all age groups, including ten-year plantations.